EDITOR’S ROLE IN THE PUBLISHING OF TRANSLATED FICTION - BRASAITĖ, FAUSTA (Knygotyra, 2013)
The goal of the article is to determine the role of editor in the publishing of translated fiction. The case study of editor’s role in the publishing of translated fiction is relevant in particular due to the popularity of translated fiction in Lithuania. As shown by the statistical analysis of Lithuanian press (years 2000–2011), translated fiction print runs are almost two times higher than native fiction print runs.The problematics of translated fiction editor’s role is related to the editor’s interim position in the literary publishing process. The editor is between the author and the translator, and this determines the uncertainty of the editor’s role. In this context, the problematics of editor’s role is closely related to such aspects of translated fiction as translator’s and editor’s cooperation, literary quality of the translation, the publishing policy of the publishing house related to the literary quality of translated fiction. Various methods were used while writing this article. The interview method was used to perform the qualitative study. While using the document and source analysis method it was concluded that the editor is like the connective tissue between the author and the reader in the publishing process. The questionnaire and the comparison methods helped to uncover that editor’s role in the publishing of translated fiction is the dimension of text quality. It also revealed that the quality of the translated fiction literature highly depends on the communication between the editor and the translator.